Indonesia’s tax revenue: The effect of inflation rate and economic growth - Deni Hamdani; Ridwan . (President University Press, 2023)
In order to ascertain and analyze the impact of Indonesia's inflation rate and economic growth on tax collections, between 2012 and 2020, the Ministry of Finance's Directorate General of Taxes performed research. Data collection approaches were acquired through literature and documentation for this research, which is categorized as descriptive and verificative research with a quantitative approach. The sampling method employs non-probability sampling, which creates a saturated sample by taking samples from the entire population. Multiple linear regression analysis is used to analyze data, while the t-test and f-test are used to assess hypotheses. The results show that inflation rate has no significant positive effect on tax revenue. Besides, economic growth has no significant negative effect on tax revenue. It is hoped that government will pay attention for tax revenue every year.